A Case of Anomalous Electric Field Perturbations in the Equatorial Ionosphere During Postsunset Hours: Insights. Issue 2 (21st February 2023) - Kumar, A.; Chakrabarty, D.; Fejer, B. G.; Reeves, G. D.; Rout, D.; Sripathi, S.; Seemala, G. K.; Sunda, S.; Yadav, A. K.
Abstract: During a weak geomagnetic storm (Ap = 15) on 24 December 2014, the penetration electric field perturbations over the Indian dip equatorial sector are found to be anomalous on a number of occasions during postsunset hours. The event is anomalous as the magnitude and polarity of penetration electric fields do not obey the existing paradigm. The penetration electric field perturbations are investigated using the vertical drifts derived from the CADI (Canadian Advanced Digital Ionosonde) measurements at Tirunelveli (8.7°N, 77.7°E, dip angle: 1.7°). During this event, we observed postsunset vertical drift of ∼42 m s −1 not only at 18:10 LT but also ∼36 m s −1 at ∼21:00 LT which is anomalous. Interestingly, the dawn‐dusk component of interplanetary electric field (IEFy) is relatively less (<2 mV/m) at ∼21:00 LT compared to the interval 19:30–20:30 LT (IEFy ∼3 mV/m). Despite that, the vertical drift observed over Tirunelveli is very close to zero or nominally upward during 19:30–20:30 LT. In addition, the downward drift just after 21:30 LT on this night is found to be exceptionally large (∼−60 m s −1 ). By combining vertical total electron content over the Indian sector with the OI 630.0 nm airglow intensity from Mt. Abu, chain of magnetometer and Los Alamos National Laboratory geosynchronous satellite particle measurements, it is suggested that the anomalous penetration electric field perturbations on this night arise from the effects of interplanetary magnetic field By and substorm. Plain Language Summary: Variation in the zonal electric field in the equatorial ionosphere during postsunset hours is important to understand the plasma distribution over low latitudes and also generation of plasma irregularities. The changes in the ionospheric conditions over low/equatorial latitudes have implications for communication and navigational applications. Therefore, if ionospheric electric field over equatorial ionosphere behaves anomalously during space weather events, it will be difficult to model the low latitude ionosphere for scientific understanding and practical applications. In this investigation, we show that the less studied Y ‐component of interplanetary magnetic field and substorm can significantly modulate the ionospheric electric field giving rise to anomalous response. Key Points: Under southward interplanetary magnetic field (IMF) Bz conditions, anomalous electric field perturbations are observed over the equatorial ionosphere The amplitude of electric field perturbations is more when the magnitude of IEFy is less and vice versa These anomalous electric field perturbations are explained based on the effects of IMF By and substorm